+0  
 
0
2
1
avatar+591 

Find all solutions to the equation $x^2 - 11x - 42 = -2x + 10 - x^2 - 5x + 16$.

 May 19, 2024
 #1
avatar+808 
0

Combining all the like terms, we have \(2x^2-4x-68=0\)

 

Using the qudratic equation to find x, we come up with \(x=1+\sqrt{35},\:x=1-\sqrt{35}\)

 

This problem isn't hard really, It's just moving all terms to one side and combining like terms, before using the quadratic equation to find x. 

 

Thanks! :)

 May 20, 2024

5 Online Users

avatar
avatar
avatar
avatar
avatar